Life-Threatening Pneumonia In A Child With Down Syndrome Challenges In A Rapidly Progressive Respiratory Failure: A Case Report - Angela Puspita; Alexander Wignyo Setiadi; Maria Elizabeth (Jurnal Impresi Indonesia, 2025)
Children with Down syndrome (DS) demonstrate increased vulnerability to severe respiratory infections due to anatomical, immunological, and physiological vulnerabilities. This case report examines the rapid progression of pneumonia in an 8-year-old child with DS, highlighting critical challenges in managing respiratory failure in this population. Methods: A retrospective case report analysis was conducted at a secondary hospital in Surabaya, Indonesia, involving comprehensive review of medical records, laboratory findings, radiological examinations, and clinical progression of an 8-year-old boy with DS who presented with severe community-acquired pneumonia. Results: The patient presented with a 10-day history of fever, productive cough, and dyspnea. Initial assessment revealed tachypnea (36 breaths/min), hypoxemia (SpO? 89%), and bilateral infiltrates on chest radiography. Despite normal leukocyte count, elevated CRP (24.3 mg/L) and thrombocytosis (589 × 10³/µL) indicated significant inflammation. Management with high-flow nasal cannula oxygenation, empirical antibiotics (ceftriaxone and azithromycin), bronchodilators, and intravenous fluids resulted in clinical improvement within 72 hours, with discharge on the sixth day. Discussion: This case underscores how common respiratory infections can rapidly deteriorate in children with DS due to airway abnormalities, immune dysfunction, and neuromuscular hypotonia. Early recognition of hypoxemia as a warning sign and timely multidisciplinary intervention are crucial to prevent respiratory failure. Preventive strategies including optimized vaccination and caregiver education are essential components of comprehensive care.